2021
DOI: 10.18502/jovr.v16i2.9079
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Trace Elements in Pseudoexfoliation Syndrome: A Cross-sectional Study

Abstract: Purpose: Pseudoexfoliation syndrome (PXF) is an age-related condition, characterized by deposition of whitish flake-shaped materials in the anterior segment of the eye. Although it occurs all over the world, a considerable racial variation exists. According to the high frequency of PXF in Iran and the importance of prevention and early treatment, we evaluated the plasma level of iron, zinc, copper, and magnesium in patients with PXF. Methods: In this study, 83 individuals were enrolled; 40 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(37 reference statements)
1
0
0
1
Order By: Relevance
“…Oxidative stress mechanism played an important role in the pathological process of cataract, in which iron, zinc, copper were involved (58)(59)(60)(61)(62)(63)(64). However, the relationship between these three trace elements and cataract could not be well confirmed in the current study (62,(65)(66)(67)(68)(69)(70)(71). This is consistent with our study, which perhaps indicated that the intake of these three trace elements had a negligible relationship with cataract.…”
Section: Discussionsupporting
confidence: 51%
“…Oxidative stress mechanism played an important role in the pathological process of cataract, in which iron, zinc, copper were involved (58)(59)(60)(61)(62)(63)(64). However, the relationship between these three trace elements and cataract could not be well confirmed in the current study (62,(65)(66)(67)(68)(69)(70)(71). This is consistent with our study, which perhaps indicated that the intake of these three trace elements had a negligible relationship with cataract.…”
Section: Discussionsupporting
confidence: 51%
“…Talebnejad ve ark.nın PES'li hastalarda yapmış olduğu çalışmada; PES grubunun serum demir oranları kontrol grubuna göre düşük bulunmuştur. 24 Cumurcu ve ark.nın Türk popülasyon üzerinde yapmış olduğu çalışmada ise PES grubunun hümör aköz örneklerindeki demir seviyesi kontrol grubuna göre farklılık göstermezken; serum demir düzeyleri kontrol grubuna göre anlamlı yüksek bulunmuştur. 25 Çalışmamızda ise PES/PEG grubunun serum demir düzeyi, TIBC, UIBC ile kontrol grubunun sonuçları arasında istatistiksel olarak anlamlı bir fark bulunmadı.…”
Section: İstati̇sti̇ksel İncelemelerunclassified